МОРАЛЬНА КУЛЬТУРА ЯК ОСНОВА ПРОФЕСІЙНИХ ЦІННОСТЕЙ МАЙБУТНЬОГО ПЕДАГОГА (Педагогіка вищої та середньої школи, 2008)
The article reveals the essence of concept “morality culture”, defines its proofs and levels forming of the morality culture of students. The article investigates the connection with professional value of future teachers.